2016
DOI: 10.12968/jowc.2016.25.sup3.s1
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating wound bed preparation: properties and clinical efficacy of octenidine and octenidine-based products in modern wound management

Abstract: S3 Octenidine dihydrochloride: chemical characteristics and antimicrobial properties S7 Wound cleansing: a key player in the implementation of the TIME paradigm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…On the other hand, OCT is a cationic, surface active antimicrobial compound (its molecular weight is approximately 624 Da), whose mode of action is based on integration with enzymatic systems. As a result, polysaccharides in the cell wall of microorganisms induce leakages in the cytoplasmic membrane and lead to cell death [7,8,35]. It has two non-interacting cation-active centers in its molecule, which are separated by a long aliphatic hydrocarbon chain [8,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, OCT is a cationic, surface active antimicrobial compound (its molecular weight is approximately 624 Da), whose mode of action is based on integration with enzymatic systems. As a result, polysaccharides in the cell wall of microorganisms induce leakages in the cytoplasmic membrane and lead to cell death [7,8,35]. It has two non-interacting cation-active centers in its molecule, which are separated by a long aliphatic hydrocarbon chain [8,35].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, polysaccharides in the cell wall of microorganisms induce leakages in the cytoplasmic membrane and lead to cell death [7,8,35]. It has two non-interacting cation-active centers in its molecule, which are separated by a long aliphatic hydrocarbon chain [8,35]. Like other cationic antiseptics, OCT's main target appears to be glycerol phosphates in the bacterial cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Octenidine is a cationic surfactant effective against Gram-positive and Gram-negative bacteria. It features two non-interacting cationic active centres separated by a lengthy aliphatic hydrocarbon chain ( Figure 1 A), which facilitate its linkage with negatively charged surfaces of the microorganisms [ 31 ]. 2-Phenoxyethanol ( Figure 1 B) is an aromatic ether with a 2-hydroxyethyl group substituting on oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…53,54 PHMB has also been shown to show antibiofilm activity on biofilms, 31,47,48,[55][56][57][58] including wound biofilms. 59,60 Octenidine has also been demonstrated to have antibiofilm activity in in vitro biofilm model assays, 61 and a number of studies have shown HOCl to exhibit antibiofilm activity. 62 Biofilms provide protection to microorganisms and blocks access of bacterial communities resident in the biofilm from antimicrobial agents, 63 which can lead to the emergence of drug-resistant infections.…”
Section: Experimental Assessment Of Anti-biofilm Activitymentioning
confidence: 99%
“…111 Kramer al (2019) 104 comparing an extensive number of antiseptics for the antibacterial activity against test organisms and assessing the cytotoxicity on cultured cells found that PHMB was one of the most suitable antimicrobial agents for use wound antisepsis. PHMB 104 and octenidine 61 balanced the level of antimicrobial activity with the level of in vitro cytotoxicity.…”
Section: Broad-spectrum Efficacy Of Phmbmentioning
confidence: 99%